The long noncoding RNA H19 promotes cell proliferation via E2F-1 in pancreatic ductal adenocarcinoma. Issue 10 (2nd October 2016) - Ma, Ling; Tian, Xiaodong; Wang, Feng; Zhang, Zhengkui; Du, Chong; Xie, Xuehai; Kornmann, Marko; Yang, Yinmo
ABSTRACT: H19 is a long noncoding RNA differentially expressed in many tumors and participates in tumorigenesis. This study aimed to investigate the expression and function of H19 in pancreatic ductal adenocarcinoma (PDAC). Pure malignant cells were isolated from frozen sections of 25 PDAC cases by laser captured microdessection, and H19 expression level was detected by qRT-PCR. Knockdown and overexpression were employed to manipulate H19 levels in pancreatic cancer cells, then cell viability, proliferation, apoptosis and cell cycle, and the growth of xenografts were evaluated. E2F-1 levels in PDAC tissues were detected by Western blot and immunohistochemical analysis. We found that H19 was overexpressed in PDAC tissues and correlated to histological grade of PDAC. Knockdown of H19 in T3M4 and PANC-1 cells with high H19 endogenous level suppressed cell viability, proliferation and tumor growth, while H19 overexpression in COLO357 and CAPAN-1 with low H19 endogenous level enhanced cell viability, proliferation and tumor growth. Knockdown of H19 led to G0/G1 arrest, accompanied by decreased levels of E2F-1 and its downstream targets. E2F-1 was overexpressed in PDAC tissues with possible correlation with H19 expression level. In conclusion, H19 is overexpressed and plays oncogenic role in PDAC through promoting cancer cell proliferation via the upregulation of E2F-1.